2016
DOI: 10.1371/journal.pntd.0004936
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Molecular Epidemiology of Japanese Encephalitis in Zhejiang, an Eastern Province of China

Abstract: BackgroundSporadic Japanese encephalitis (JE) cases still have been reported in Zhejiang Province in recent years, and concerns about vaccine cross-protection and population-level immunity have been raised off and on within the public health sphere. Genotype I (GI) has replaced GIII as the dominant genotype in Asian countries during the past few decades, which caused considerable concerns about the potential change of epidemiology characteristics and the vaccine effectiveness. The aim of this study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 29 publications
(39 reference statements)
4
33
0
Order By: Relevance
“…Several studies have focused on vaccine efficacy affected by genotype replacement. Overall results suggested that the GIII JEV vaccine might temporarily protect against GI virus infection, especially for travelers, but vaccine efficacy for long-term protection might be reduced in GI JEV epidemic or endemic countries or regions 18 25 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have focused on vaccine efficacy affected by genotype replacement. Overall results suggested that the GIII JEV vaccine might temporarily protect against GI virus infection, especially for travelers, but vaccine efficacy for long-term protection might be reduced in GI JEV epidemic or endemic countries or regions 18 25 .…”
Section: Introductionmentioning
confidence: 97%
“…Considerations of a next-generation JEV vaccine for sows might include an ability to block virus transmission and induce cross-protective activity against the currently dominant GI virus and other genotypic viruses, especially the co-circulating GIII virus in some JEV endemic regions 18 , 26 , 27 . Non-infectious and self-assembled virus-like particles (VLPs) can elicit protective immunity against viral infection and are a suitable vaccine candidate for many viruses including JEV 28 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Still, this type of platform could be a tool for screening serum samples of symptomatic individuals for multiple flaviviruses at once (87). Microseroneutralization tests have also been used in serosurveillance of JEV (88).…”
Section: Serological Diagnosismentioning
confidence: 99%
“…29 The results on the longevity of responses should be interpreted with caution since the outcome may depend on whether the study was conducted in a non-endemic or an endemic area. Seropositivity rates are known to increase significantly beyond 10-15 years of age in endemic areas, 167,[180][181][182] and an inverse correlation has been observed between an age of >5-6 years and the incidence of JE disease. 167 In addition, direct correlation between seropositivity rates and the incidence of JE in an area has also been documented.…”
Section: Longevity Of Protective Responses Induced By Je Vaccinesmentioning
confidence: 99%
“…Seropositivity rates are known to increase significantly beyond 10-15 years of age in endemic areas, 167,[180][181][182] and an inverse correlation has been observed between an age of >5-6 years and the incidence of JE disease. 167 In addition, direct correlation between seropositivity rates and the incidence of JE in an area has also been documented. 183 Furthermore, asymptomatic infections with other flaviviruses in endemic areas is expected to boost responses elicited by JE vaccination.…”
Section: Longevity Of Protective Responses Induced By Je Vaccinesmentioning
confidence: 99%